Frontispiece: Highly Active and Robust Metalloporphyrin Catalysts for the Synthesis of Cyclic Carbonates from a Broad Range of Epoxides and Carbon Dioxide. Issue 19 (21st April 2016) - Maeda, Chihiro; Shimonishi, Junta; Miyazaki, Ray; Hasegawa, Jun‐ya; Ema, Tadashi
Abstract : Porphyrinoids CO2 is a cheap, abundant, and nontoxic C1 source, and the chemical conversion of CO2 into useful organic compounds has become increasingly important. In their Full Paper onpage 6556 ff., C. Maeda, J. Hasegawa, T. Ema et al. describe the synthesis of bifunctional metalloporphyrins with quaternary ammonium bromides at the meta, para, or ortho positions of the meso ‐phenyl groups and investigated their catalytic activities in the formation of cyclic carbonates from epoxides and CO2 under solvent‐free conditions.